Caracterização da biomassa de genótipos de batata-doce para produção de bioetanol - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Bioethanol produced from biomass is considered as a renewable fuel alternative with potential for fossil fossils, an important mechanism in mitigating the sources of gases responsible for the increase of the greenhouse effect. Starch is one of the promising sources for bioethanol production. The sweet potatoes (Ipomoea potatoes) for example, is an important source of starch. The aim of was to characterize the biomass of 10 sweet potato genotypes for bioethanol production. The experimental design used was randomized blocks, with 10 treatments (BD1, BD2, BD3, BD4, BD5, BD6, BD7, BD8, BD19, BD20) and 03 replications. The genotypes were cultivated in the municipality of Lapa, Paraná - Brazil, in the 2020 harvest. The variables analyzed were: root shape, surface defect, storage root cortex thickness, predominant periderm color, periderm color intensity, periderm secondary color, pulp color, predominant secondary pulp color, distribution of secondary pulp color, vine pigmentation, pubescence of the vine apex, length of the main vines, inter-node length of the vine, inter-node diameter, general leaf profile, type of mature leaf lobe, number of mature leaf lobes, mature leaf central lobe shape, leaf size, lower vein pigmentation, leaf color, immature leaf color, petiole pigmentation, petiole length, shoot fresh mass, root fresh mass, shoot dry mass, root dry mass and granule size of starch. It is concluded that the genotypes present distinct morphological characteristics for vegetative aerial and tuberous roots, and distinct characteristics for the size of starch granules. The genotypes with more potential for ethanol production are BD3, BD4, BD5, BD6, BD7, BD19, BD20.
Keywords: amido; Ipomoea batatas; parte aérea; raiz tuberosa; starch; Ipomoea batatas; aerial part; tuberous root; CNPQ::CIENCIAS AGRARIAS